Inovasi Pembelajaran SKI melalui Pemanfaatan Media Video untuk Meningkatkan Motivasi dan Partisipasi Belajar Siswa di MA MAI Purwakarta - Aulia, Salshabila; Munir, Dede Rizal; Setiawan, Usep (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to determine the use of video learning media in the subject of Islamic Cultural History (SKI), students’ learning motivation in the SKI learning process, and the contribution of video learning media to improving students’ learning motivation at MA MAI Purwakarta. The type of research used is classroom action research (CAR) conducted in two cycles. Each cycle consists of four stages: planning, action, observation, and reflection. Data were collected through observation, interviews, and documentation. The data obtained were analyzed descriptively and qualitatively. The results showed that students’ learning motivation increased after the implementation of video media in cycles I and II. Based on observations and interviews, the improvement was seen in aspects of learning persistence, students’ interest and attention during the learning process, and independence in completing assignments. Thus, it can be concluded that the use of video learning media contributes positively to increasing students’ learning motivation in the Islamic Cultural History (SKI) subject for tenth-grade students at MA MAI Purwakarta.